An in vitro evaluation of fit of the crowns fabricated by zirconium oxide-based ceramic CAD/CAM systems, before and after porcelain firing cycles and after glaze cycles - A. Hmedat, Sattar J; Ibraheem, Adel F (Journal of Baghdad College of Dentistry, 2013)
Background: The objective of this in vitro study was to evaluate the vertical marginal fit of crowns fabricated with ZrO2 CAD/CAM, before and after porcelain firing cycles and after glaze cycles.Materials and Methods: An acrylic resin model of a left maxillary first molar was prepared and duplicated to have Nickel-Chromium master die. Ten die stone dies were sent to the CAD/CAM (Amann Girrbach) for crowns fabrication. Marginal gaps along vertical planes were measured at four indentations at the (mid mesial, mid distal, mid buccal, mid palatal) before (Time 0) and after porcelain firing cycles (Time 1) and after glaze cycles (Time 2) using a light microscope at a magnification of ×100. One way ANOVA LSD tests were performed to determine whether the mean and standard deviation of sub group Time 2.Results: The mean values of the ZrO2 CAD/CAM Time 0 were (6.77?m), Time 1(8.75?m) and Time 2(10.62 ?m). One way ANOVA test revealed highly statistical significance(P